The Impact of Destination Image, Novelty Seeking, Involvement Seeking and Tourist Satisfaction on Edutourism Tourists’ Revisit Intention - Syafrida, M. Fajar; Sari, Dessy Kurnia; Syafrizal (Jurnal Informatika Ekonomi Bisnis, 2023)
This study aims to examine the effect of destination image, novelty seeking, and involvement seeking on revisit intention mediated by tourist satisfaction for Sirukam Dairy Farm tourists in Solok Regency, West Sumatera, Indonesia. An exploratory quantitative approach with hypothesis-testing techniques is used in this study. There are 150 samples with purposive sampling technique, namely tourists who have visited Sirukam Dairy Farm twice or more. Data were collected through the distribution of online questionnaires and processed using SmartPLS 4.0 software. The data analysis method uses structural equation modeling with partial least squares (SEM-PLS). The results showed that destination image and involvement seeking have a positive and significant effect on tourist satisfaction, while novelty seeking shows an insignificant effect on tourist satisfaction. Destination image, novelty seeking, and tourist satisfaction have a positive and significant effect on revisit intention, while involvement seeking shows an insignificant effect on revisit intention. Tourist satisfaction is able to partially mediate the relationship between destination image and novelty seeking and revisit intention, while the relationship between involvement seeking and revisit intention is fully mediated by tourist satisfaction.